THE ANALYSIS OF TUNA RESOURCE UTILIZATION LEVEL WITH SPAWNING POTENTIAL RATIO METHOD IN SENDANGBIRU WATERS - Made Mahendra Jaya; Budy Wiryawan; Domu Simbolon (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2017)
High market demand for tuna drives the increasing intensity of tuna fishery in Sendangbiru waters. This occours also in almost all of Indonesian waters. High intensity of tuna fishing especially in Southern Java will threaten the preservation and sustainabilityof tuna resource. The decreasing trend of CPUE occured in the last 3 years (2013-2015) indicates that the exploitation rate of tuna resources in Sendangbiru was over fishing. This study aims to assess the status of tuna reasources due to fishing in Sendangbiru. The method used in this research is length based spawning potential ratio approaches or LB-SPR. Results from this study showed that the utilization of tuna resources in Sendangbiru is already at the level of over-exploited as shown by SPR value of 16.98 (less than 20%). Keywords : decreasing tren of CPUE, LB-SPR, Tuna fisheries